Implementasi Sistem Pakar Diagnosis Autisme Pada Anak Menggunakan Metode Naïve Bayes - Syah Zanul Husna; Raissa Amanda Putri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Autism is a developmental disorder that affects the normal functioning of the brain, thereby affecting a child's communication and social interaction abilities. This disorder poses a problem for children in communicating and forming relationships with their environment. As the number of individuals with autism increases, public awareness of autism remains very low. Additionally, most psychologists or psychiatrists are located in major cities, limiting access for rural communities. This leads to many parents struggling to obtain information about autism symptoms. The research method used is the naïve Bayes method, it can be drawn from the system is that it will generate the maximum score despite any disturbances in the provided data. The results of this research align with expert knowledge, suggesting that it can be relied upon to accurately diagnose autism based on the symptoms experienced by individuals. The aim of this study is to build an expert system that can provide information and solutions to parents regarding autism disorders based on their knowledge of the symptoms they experience, enabling users to diagnose autism in their children early on without incurring costs.